Multi-Objective Optimization of MEMS-based Box Pattern Microheaters Using Response Surface Method - Setyawati, Onny; Choiron, Moch. Agus; Bangert, Axel; Sandhagen, Carl (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2024)
We present a response surface method to evaluate multi-objective optimization for MEMS-based microheater design. Box pattern, the standard microheater shape, was selected in this study since it has a uniform temperature distribution compared to other patterns. The optimum parameters are used to obtain the maximum total current density and Joule heat. Based on a hybrid of the Response Surface Method and Central Composited Design, the model simulation emerged with 25 sets of Design Experiments. As expected, the voltage is proportional to the increased output temperature and Joule heat of the microheater. Material thermal conductivity, anchor length and thickness of the heating element are included as design variables for the optimization. The microheater thicknesses of 4.23 - 4.55 µm, length of 40 µm and thermal conductivity of materials of approximately between 52 to 66 Wm-1K-1 became the optimized results at 1 V input voltage to obtain a maximum Joule heat of 4.9x105 W/mm3 and total current density of 5.6x107 mA/mm2.